2012
DOI: 10.1016/j.bpj.2012.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Thin Plates from Micrococcal Nuclease-Digested Chromatin of Metaphase Chromosomes

Abstract: The three-dimensional organization of the enormously long DNA molecules packaged within metaphase chromosomes has been one of the most elusive problems in structural biology. Chromosomal DNA is associated with histones and different structural models consider that the resulting long chromatin fibers are folded forming loops or more irregular three-dimensional networks. Here, we report that fragments of chromatin fibers obtained from human metaphase chromosomes digested with micrococcal nuclease associate spont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 54 publications
4
26
0
Order By: Relevance
“…A recent in vitro study showed that short fiber stretches containing several nucleosomes, extracted from chromatin by mild MNase digestion, readily form ordered structures in vitro, indicating that chromatin fibers do sense the shapes of each other [103]. In addition, our modeling suggests that chromatin fibers not only sense the general shapes but can also distinguish in-and out-of-register arrangements of nucleosomes, suggesting interplay of recognition mechanisms on different length-scales.…”
Section: Discussionmentioning
confidence: 73%
“…A recent in vitro study showed that short fiber stretches containing several nucleosomes, extracted from chromatin by mild MNase digestion, readily form ordered structures in vitro, indicating that chromatin fibers do sense the shapes of each other [103]. In addition, our modeling suggests that chromatin fibers not only sense the general shapes but can also distinguish in-and out-of-register arrangements of nucleosomes, suggesting interplay of recognition mechanisms on different length-scales.…”
Section: Discussionmentioning
confidence: 73%
“…In this context, recent research has revealed that multilayer plates (identical to those found in metaphase chromosomes) can be self-assembled from chromatin fragments obtained by micrococcal nuclease digestion of metaphase chromosomes [18]. This finding has reinforced the thin-plate model for metaphase chromosome structure (figure 1a,c) and suggests that the whole chromosome could be a self-organizing structure.…”
Section: Introductionmentioning
confidence: 68%
“…Typical chromatin plates can be self-assembled from chromatin fragments of metaphase chromosomes, indicating that chromatin structure can hold discontinuous DNA in the correct place within the plates [18]. However, when the relatively high lateral force of the AFM tip was applied to micrococcal nucleasedigested plates in nanotribology experiments, the structural integrity of chromatin layers was maintained only if the degree of digestion was very low [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with this notion, earlier results from the Daban group had shown that isolated chromatin fibers, obtained from micrococcal nucleasedigested metaphase chromosomes, can selfassociate to form chromatin plates in vitro (Milla & Daban, 2012). To this end, they carefully purified individual mitotic chromosomes from human cells.…”
mentioning
confidence: 65%